Avaliação do efeito neuroprotetor produzido pela alamandina em modelo de isquemia e reperfusão cerebral - Sthéfanie Chaves de Almeida Gonçalves (2018)
Stroke is characterized by reduced or interrupted blood flow to the brain, which can result in neuronal death. It is a prevalent disease, highly disabling and it is among the leading causes of death worldwide. Previous studies have shown the involvement of the reninangiotensin system (RAS) in the pathophysiology of stroke. Angiotensin-(1-7) is able to promote neuroprotection in an experimental model of stroke mainly due to its antiinflammatory action. Alamandine, a peptide formed by the decarboxylation of aspartic acid from Ang-(1-7) or by the hydrolysis of Ang A by the angiotensin converting enzyme 2, has recently been identified as a new mediator of the RAS. Studies to date have shown that most of alamandine actions are similar to those of Ang-(1-7), which may become an important alternative route of the RAS to attenuate the development of neurovascular diseases. The aim of the present study was to evaluate the neuroprotective effect of alamandine in a model of cerebral ischemia/ reperfusion induced by bilateral common carotid arteries occlusion (BCCAo). Male, 9 to 12 weeks old Sprague-Dawley rats were separated into 3 experimental groups: Control untreated (Sham-vehicle, n=16), BCCAo untreated (vehicle; n=17) and BCCAO treated with alamandine included in cyclodextrin (0.2 μg; n=19). Treatment was performed by intracerebroventricular (ICV) route. The treatment was performed about 20 min before carotid occlusion. We showed that central injection of alamandine produces an antiinflammatory effect, with the reduction of TNFα, IL-1β and IL-6, and antioxidant effect through an increase in SOD, catalase and GSH in the brain of BCCAo rats. In keeping, alamandine reduced the number of apoptotic neurons/cells and attenuated the neurological deficit of animals subjected to BCCAo. Further, MrgD knockout mice, an animal model that lacks the main alamandine receptor, showed increase in neurological deficit. These results indicate that alamandine presents a neuroprotective effect in a model of ischemia and reperfusion.